An array of individually addressable micro-needles for mapping pH distributions. Issue 15 (31st May 2016) - Zuliani, Claudio; Ng, Fu Siong; Alenda, Andrea; Eftekhar, Amir; Peters, Nicholas S.; Toumazou, Christofer
Abstract : This work describes the preparation of an array of individually addressable pH sensitive microneedles which demonstrated suitable for measuring pH distribution during heart ischemia and reperfusion cycles. Abstract : This work describes the preparation of an array of individually addressable pH sensitive microneedles which are sensitized by electrodepositing iridium oxide. The impact of the deposition potential, storage conditions and interferents on the sensor characteristics such as slope, offset, intra- and inter-batch reproducibility is investigated. The device may be a useful tool for carrying out direct pH measurements of soft and heterogeneous samples such as tissues and organs. For example, we demonstrated that the microneedle array can be employed for real-time mapping of the cardiac pH distribution during cycles of global ischemia and reperfusion.